Milling damage on carbon fibre reinforced polymer using tiAIN coated end mills - Konneh, Mohamed; Sudin, Izman; Kassim, Abdullah Abdul Rahman (IOP Publishing, 2015)
This paper reports on the damage caused by milling Carbon Fibre Reinforced Composite (CFRP) with 2-flute 4 mm-diameter solid carbide end mills, coated with titanium aluminium nitride. The machining parameters considered in work are, rotation speed, feed rate and depth of cut. Experiments were designed based on Box-Behnken design and the experiments conducted on a Mikrotool DT-110 CNC micro machine. A laser tachometer was used to ascertain a rotational speed for conducting any machining trial. Optical microscopy examination reveals minimum delamination value of 4.05 mm at the spindle speed of 25,000 rpm, depth of cut of 50μm and feed rate of 3 mm/min and the maximum delamination value of 5.04 mm at the spindle speed of 35000 rpm, depth of cut of 150μm and feed rate of 9 mm/min A mathematical model relating the milling parameters and delamination has been established